Diabetes Mellitus dan Sulfonilurea - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
Diabetes mellitus characterized by increased blood glucose level (hyperglycemia) is currently recognized to be a heterogenous disorder. Although there has been general acceptance of the classification adopted by WHO Expert Committee on Diabetes Mellitus in 1980, the WHO Study Group revised the classification in 1985. The most important change from the previous classification is the appearance of malnutrition-related diabetes mellitus as a major subclass, ranking with IDDM (insulin-dependent diabetes mellitus) or type I diabetes mellitus and NIDDM (non-insulin- dependent diabetes mellitus) or type II diabetes mellitus.Sulfonylurea orally administered hypoglycemic agents have been used in the treatment of NIDDM for more than 30 years. Despite this fact, the mechanism responsible for hypoglycemic action of sulfonylurea agents remains controversial. Sulfonylureas are now generally thought to act by improving both the ability of pancreatic islets to secrete insulin and the response of tissues to insulin. There are two kinds of sulfonylureas, so-called first•generation sulfonylureas (tolbutamide and chlorpropamide) and second-generation sulfonylureas (glybenclamide, glyclazide, glypizide, and glyquidone), now available in Indonesia. The indications, contraindications, and guidelines for the use of these agents, as well as their mechanisms of action and the differences among them, are reviewed in this article.Key Words: classification of diabetes mellitus - sulfonylureas - hyperglycemia - malnutrition -- insulin